Review on Intellectual Capital Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Managing intellectual capital has gained popularity among both academic and industrial settings due to the efforts by multiple businesses to obtain a profitable competitive edge. To improve the potential of financial statements to provide an accurate description of the financial situation of the company, A wide range of intangible determinants, such as information, invention and intellectual property, which are seen as critical determinants of the performance of businesses, will need to be identified. The literature provides a set of models of intellectual capital management that explain the different facets that a company needs to consider when handling intellectual capital. Instead, at different stages of knowledge growth, the portion of elements of intellectual capital is also established, described and addressed to fit better with the theory. The intellectual capital elements of the company can only be successfully exploited when intellectual capital management is available. While intellectual capital management is known as fostering sustainable competitive advantage, intellectual capital management in Asian countries like Malaysia is not as comprehensive as the countries in the West. The aim of this paper is therefore to explore the CICM model for Malaysian firms which will improve the existing models.